2012
DOI: 10.1038/srep00610
|View full text |Cite
|
Sign up to set email alerts
|

X-ray imaging of tumor growth in live mice by detecting gold-nanoparticle-loaded cells

Abstract: We show that sufficient concentrations of gold nanoparticles produced by an original synthesis method in EMT-6 and CT-26 cancer cells make it possible to detect the presence, necrosis and proliferation of such cells after inoculation in live mice. We first demonstrated that the nanoparticles do not interfere with the proliferation process. Then, we observed significant differences in the tumor evolution and the angiogenesis process after shallow and deep inoculation. A direct comparison with pathology optical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…It has been reported that 1.9 nm AuNP 47 and 15 nm AuNP coated with m-PEG did not produce any adverse effect in mice. 32 In vitro toxicity of 15 nm AuNP coated with 11-MUA, 33 HDL coated AuNP, 5 PEI capped 15 nm AuNP, 34 silica coated AuNP 16 and a 153 nm PEGylated gold nanoshells 48 are found to be cytocompatible in a range of cell lines and under a range of conditions. Another in vitro study reported that cetyltrimethylammonium bromide coated gold nanorods reduce the HeLa cell viability 21%, whereas for the case of polyelectrolytes (such as poly(diallyldimethylammonium chloride)–poly(4-styrenesulfonic acid) coated gold nanorods are cytocompatible.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that 1.9 nm AuNP 47 and 15 nm AuNP coated with m-PEG did not produce any adverse effect in mice. 32 In vitro toxicity of 15 nm AuNP coated with 11-MUA, 33 HDL coated AuNP, 5 PEI capped 15 nm AuNP, 34 silica coated AuNP 16 and a 153 nm PEGylated gold nanoshells 48 are found to be cytocompatible in a range of cell lines and under a range of conditions. Another in vitro study reported that cetyltrimethylammonium bromide coated gold nanorods reduce the HeLa cell viability 21%, whereas for the case of polyelectrolytes (such as poly(diallyldimethylammonium chloride)–poly(4-styrenesulfonic acid) coated gold nanorods are cytocompatible.…”
Section: Discussionmentioning
confidence: 99%
“…Optical methods such as confocal microscopy, multi-photon microscopy (Maurin et al 2011) and optical coherence tomography (Vakoc et al 2012) have higher resolution but are limited to a relatively thin region closest to the surface. Very high-resolution imaging (<10 μm) of the microvasculature of mouse tumors using x-ray absorption-contrast agents has been demonstrated at synchrotrons (Chien et al 2012, Chien et al 2010, but the availability of these large facilities is limited and the required radiation dose using absorption contrast is incompatible with longitudinal studies.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al designed cationic surface modified GNPs with enhanced cellular uptake as a novel radio-sensitizer to lower the effective dose of X-ray in cancer radiation therapy [36]. Chien et al used GNPs as contrast agents for X-ray imaging of tumor growth in vivo based on the extinction effect of GNPs [37]. In this study,…”
Section: Discussionmentioning
confidence: 96%